Pengelolaan Lingkungan dan Tata Kelola Kawasan Wisata Danau Sipin Kelurahan Legok Kecamatan Danau Sipin Kota Jambi - Heriberta; Hastuti, Dwi; Zulfanetti; Utama, Hari Wiki; Ernawati, Dwi Wiwik (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
Sipin Lake Area, located in the middle of Jambi City, Jambi Province, is not only developed as a tourist destination but also as a place to stimulate economic activities for the community. Its strategic location has become a focus for the government and the academic community, particularly in the management of the tourism area. One aspect of management that is currently not fully implemented and requires full attention is the inadequate spatial planning. The lack of public awareness in managing the Sipin Lake Tourism Area will undoubtedly affect the number of visitors to the lake. Good spatial governance is an important consideration when visiting a tourist destination. However, when observing the current condition of the Sipin Lake tourism area, it is far from being considered well-managed in terms of spatial planning. The role of the academic community is crucial in realizing good spatial management around the Sipin Lake Area. It is necessary to increase the awareness of the local community to continue managing the Sipin Lake Tourism Area. The community's concern for the importance of proper spatial management in the tourism area is expected to enhance the attraction of tourists to visit the Sipin Lake tourist attraction. The community engagement activities carried out by the academic community of the University of Jambi will undoubtedly contribute to the advancement of the Sipin Lake tourist attraction and raise public awareness of the importance of good management in preserving and sustaining the Sipin Lake tourist attraction.